Ophioglossum gujaratense, a new species from Gujarat State, India - Patil, Sachin M.; Kachhiyapatel, Ronak N.; Patel, Ravi S.; Rajput, Kishore S. (Phytotaxa, 2018)
A new species, Ophioglossum gujaratense, is described from Gujarat state (India). It resembles O. polyphyllum in the presence of sheathing rhizomorph and 1–4 (rarely 5) trophophylls. On the other hand, rhizomorph morphology, common stalk, trophophyll arrangement, leaf lamina and leaf base make it distinct from O. polyphyllum. Stoloniferous roots, trophophyll number and their arrangement of the new species also resemble O. parvifolium and O. nudicaule. However, both these species lack a sheath around the leaf-stem base. A comparative account of morphologically similar species, viz. O. gujaratense, O. polyphyllum, O. parvifolium and O. nudicaule is provided. The distinctness of the new taxon has been confirmed using molecular data from chloroplast genome markers viz rbcL, trnH-psbA, trnF-trnE and trnL-trnF.